Invasive clonal plants possess greater capacity for division of labor than natives in high patch contrast environments - Zhang, Jin; You, Wen-Hua; Li, Ning-Ning; Du, Dao-Lin (Frontiers in Plant Science, 2023)
Invasion success of clonal plants is closely related to their unique clonal life history, and clonal division of labor is a crucial clonal trait. However, so far, it is unclear whether invasive alien clonal species generally possess a greater capacity for division of labor than native species and whether this pattern is affected by environmental conditions. To test whether patch contrast affects the differences in the capacity for division of labor between invasive alien and native clonal plants, we selected five pairs of exotic invasive and native clonal plant species that are congeneric and co-occurring in China as experimental materials. We grew the clonal fragment pairs of these invasive and native plants under high, low, or no contrast of reciprocal patchiness of light and nutrient, respectively, with ramet connections either severed (division of labor prevented) or kept intact (division of labor allowed). The results showed that connection significantly decreased the proportion of biomass allocated to roots in distal (younger) ramets, whereas it increased in proximal (older) ramets of all studied plants under high -contrast treatments. This clear pattern strongly indicated the occurrence of division of labor. Furthermore, the connection had a more pronounced effect on the pattern of biomass allocation of invasive alien plants, resulting in a greater increase in biomass for invasive alien plants compared to native plants. These findings suggest that the invasive alien plants possess a greater capacity for division of labor, which may confer a competitive advantage to them over natives, thus facilitating their invasion success in some heterogeneous habitats such as forest edges where light and soil nutrients show a high negative correlation.